Evaluasi Penerapan Visi Misi Pelayanan Villa Terhadap Kinerja Karyawan Berdasarkan Ulasan Tamu - Susiana, R. Apria (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
This study aims to evaluate the extent to which a villa's organizational vision and mission are implemented in employee service, based on guest perceptions reflected in online reviews. Using a descriptive qualitative approach and content analysis method, the research analyzes vision-mission documents and ten guest reviews from various digital platforms. The findings reveal that core organizational values such as hospitality, professionalism, aesthetics, and empathy have been effectively internalized by employees and are consistently acknowledged by guests. The reviews not only assess technical aspects of service but also reflect emotional engagement resulting from personalized and value-driven service. These results highlight that a well-implemented vision and mission can serve as a foundational element in building service quality and competitive advantage in the hospitality sector. Guest reviews are proven to be a valid external indicator for evaluating the effectiveness of organizational value strategies.